Violation of taboo as a source of humour in French comic proverbs and riddles: Naruszanie tabu jako źródło komizmu we francuskich przysłowiach i zagadkach - Lipińska, Magdalena (Rozprawy Komisji Językowej, 2019)
https://doi.org/10.26485/RKJ/2018/65/6 Article in Polish In French comic proverbs and riddles mechanisms of comism connected with taboo can be defined by means of semantic and stylistic analysis, however, the most comprehensive description can be obtained by employing linguistic pragmatics as research instruments. Comic violation of taboo stems from breaching the maxims of politeness and quantity. Another source of humour derives from the contrast between cultural presupposition and the sense of the sentence or its implication. Implied topics are the basis for humour, quite like the implied structure of an utterance. Such sentences represent indirect speech acts: illocutionary tropes, as well as allusive derivatives packed with vulgarisms. From the semantic point of view, contrasts between specific inherent semes and afferent ones prevail. Oppositions within specific inherent semes or afferent contextual ones can also be observed. Comic proverbs and riddles represent puns, simple or complex tropes as well as rhymed paraphrases. Taboo content can be found in lexemes with broad connotations.